The Influence Of Storytelling Marketing On Purchase Intention Mediated By Brand Image: A Case Study Of Mekayo Coffee Shop - Rara Indah Oktaviani; May Dedu; Soesanty Maulany (Rescollacom (Research Collaborations Community), 2026)
Abstract The coffee shop industry in Indonesia is expanding swiftly, although not all establishments can compete effectively. The Mekayo coffee business has seen variable sales figures. This case study seeks to assist the firm in overcoming the problems posed by intensifying competition. This study aims to investigate the role of brand image as a mediator in the relationship between narrative marketing and purchase intention. This study employed a quantitative technique. The sampling approach employed a purposive sampling technique. The research sample comprised 360 respondents, all of whom were followers of Coffee Mekayo on Instagram. A survey using the Likert approach was employed for data gathering. The data analysis approach employed was SmartPLS software version 4. The data demonstrated that narrative marketing has a substantial impact on brand image, brand image significantly influences purchase intention, and storytelling marketing greatly influences purchase intention. Additional data suggest that brand image somewhat mediates the impact of narrative marketing on brand image. These findings demonstrate the significance of narrative marketing in establishing brand image and fostering customer purchase intention. Keywords: storytelling marketing, brand image, purchase intention, coffee industry.